KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA DENGAN MENERAPKAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL MELALUI MODEL PEMBELAJARAN KOOPERATIF THINK–PAIR–SHARE BEREMPAT DAN KEMUNCULAN KOMPONEN PEMBELAJARAN KONTEKSTUAL - NOLA NARI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
One of the causes of students’ low in comprehending concepts in learning mathematics is the teacher centered teaching method. One alternative that can be proposed to solve the problem is by employing contextual learning approach through TPS-Berempat cooperative learning. This study therefore aimed at figuring out whether the students’ concept which was taught by TPS-Berempat cooperative learning model is better than that by the conventional one and whether the components of the model existed. The participants of the research were the seventh grade students of SMP N 20 Padang in 2009/2010 academic year. Quasi Experimental method using Posttest Control Group Design was employed. Experimental group was treated by using contextual learning approach while the control one by using conventional. The data was taken from achievement test. The result of the analysis showed that the components of the contextual learning appeared well and students’ comprehension toward the concept which was taught by contextual learning in mathematics was better than that of by the conventional one.Kata kunci: pemahaman konsep, pendekatan kontekstual, kooperatif TPS-berempat